Music, education, and religion : intersections and entanglements - Kallio, Alexis Anja; Alperson, Philip, 1946-; Westerlund, Heidi (Counterpoints: music and education, 2019)
Music, Education, and Religion: Intersections and Entanglements explores the critical role that religion can play in formal and informal music education.